ANALYSIS OF PROBLEMS IN THE TRANSLATION OF ROBINSON CRUSOE BY DANIEL DEFO FROM ENGLISH TO UZBEKI - Azizova Nilufar (Ta'lim innovatsiyasi va integratsiyasi, 2024)
This article was written by Daniel Defoe - the translation of the anthroponyms in "Robinson Crusoe" from English to Uzbek and the factors influencing their meaning from the linguistic point of view were analyzed taking into account the factors influencing the reader's understanding. Since the anthroponyms chosen as objects are fabrics, before the names of the anthroponyms, their function in the work was thought out, and then it was put into linguistic patterns. Because of this, templates are offered for etymological, lexicological, semantic and phonetic analysis before the translator of the article translates them into Uzbek.